Why the House Is Made of Gingerbread : Poems - Haymon, Ava Leavell (Book collections on Project MUSE., 2010)
In Ava Leavell HaymonAEs third collection, an unremarkable, harried, contemporary woman named Gretel finds herself at midlife overtaken by the GrimmsAE household tale Hansel and Gretel. The violence and terror in that story supplant the memory of her own childhood, and the fairy tale retells itself in a sharp succession of surprising poems. The witch, the sugar house, GretelAEs brother, her passive father, his cruel second wife, the sinister forestall these and more rise like jazz motifs to play themselves in the present. Addressing themes such as hunger, child abuse, betrayal, cannibalism, and.